An exploratory study: Corporate Social Responsibility perceptions in Guinea-Bissau and Ivory Coast - Paiva, I.; Carvalho, L.; Sánchez-Hernandez, I. (International Congress on Public and Nonprofit Marketing, 2017)
Corporate Social Responsibility (CSR) is now crucial to enhance long-term competitiveness. CSR is also linked with several strategic business dimensions such as innovation, performance, and competitive success. However, most of the available studies conducted at the moment use samples from developed countries in America and Europe, and insufficient attention has been given to less developed countries, particularly in Africa. Taking into account that the current models to understand and measure the concept of CSR, and to determine how to obtain competitive advantage through responsible business behaviour, have not yet been applied to Africa, this article is a first step to fill the gap. Based on recently published models addressing the above-mentioned variables, this paper aims to study CRS through the application of a questionnaire to managers in two countries in West Africa: Guinea-Bissau and the Ivory Coast. The main goal of this exploratory study was the understanding of the current situation of CSR managers´ perceptions in both countries. For this purpose, the paper uses an overall scale to examine the different theoretical dimensions reflecting CSR: social, economic, and environmental dimensions. The results show that there is a generally positive perception of the CSR elements, although the emphasis is given to economic issues and the social issues related to human resources, training and empowerment of employees and leadership skills, among others. As conclusion the study points out the role of managers in promoting a culture of social innovation by focusing on the CSR philosophy.